100 training games - Kroehnert, Gary (McGraw Hill, 1994)
Each game is self-contained and provides all the necessary instructions and materials. What's more, a unique index grid and system of graphic symbols help you locate and choose complementary games and respond confidently to particular training needs and situations. 100 Training Games is a must-have sourcebook for trainers and managers in all functions and industries.